Prediction of Clinical Outcomes in Hepatitis B E Antigen Negative Chronic Hepatitis B Patients with Elevated Hepatitis B Virus DNA Levels. - Jem Ma Ahn; Dong Hyun Sinn; Geum-Youn Gwak; Yong-Han Paik; Moon Seok Choi; Joon Hyeok Lee; Kwang Cheol Koh; Seung Woon Paik (PLoS ONE)
Objectives We investigated whether long-term clinical outcomes such as disease progression or inactive hepatitis B virus (HBV) carrier state can be predicted by baseline factors in hepatitis B e antigen (HBeAg)-negative HBV infected patients with an elevated viral load. Methods A retrospective cohort of 527 HBeAg-negative chronic HBV infected patients with an elevated viral load (HBV DNA ≥ 2,000 IU/ml) was assessed for disease progression defined by the development of hepatocellular carcinoma (HCC) or cirrhotic complication, as well as becoming an inactive carrier. Results During a median 3.6 years of follow-up, disease progression was detected in 46 patients (40 with HCC, 6 with cirrhotic complication), and 31 of 309 non-cirrhotic patients became inactive carriers. Older age, male gender, cirrhosis, high HBV DNA levels at baseline, and short antiviral therapy duration were independent risk factors for HCC. Low HBV DNA and quantitative hepatitis B surface antigen (qHBsAg) levels were independent predictors for becoming inactive carriers in patients without cirrhosis. In non-cirrhotic patients with both low qHBsAg and HBV DNA levels, the 5-year cumulative incidence of an inactive carrier was 39.8%, while that of disease progression was 1.6%. Conclusion HBeAg negative patients without cirrhosis can be closely monitored for becoming an inactive carrier when both HBV DNA and qHBsAg levels are low, as the risk of disease progression is low while incidence of an inactive carrier is high.